Internet governance as 'ideology in practice' – India's 'Free Basics' controversy - Anita Gurumurthy; Nandini Chami (Internet Policy Review, 2016)
The paper examines the recent Free Basics controversy in India, which triggered a national level policy debate on the appropriate regulatory response to differential pricing of data services, employing the theoretical framework of 'ideology in practice'. Unpacking 'openness' in design, 'inclusion' in provisioning and 'empowerment' in use as contested concepts in the policy process, the paper demonstrates a paradoxical conflation of oppositional interpretations of access. Tracing the material-discursive practices of actors in the debate and scrutinising everyday practices of the internet for their moral claims, the paper examines if and how hegemonic discourses of economic globalisation are challenged, and alternative meanings of the internet etched in contemporary political agenda on internet governance in India.
Keywords: 300; Internet governance; Net neutrality; Facebook; Internet access